2009
DOI: 10.1186/1478-7547-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness model comparing olanzapine and other oral atypical antipsychotics in the treatment of schizophrenia in the United States

Abstract: Background: Schizophrenia is often a persistent and costly illness that requires continued treatment with antipsychotics. Differences among antipsychotics on efficacy, safety, tolerability, adherence, and cost have cost-effectiveness implications for treating schizophrenia. This study compares the cost-effectiveness of oral olanzapine, oral risperidone (at generic cost, primary comparator), quetiapine, ziprasidone, and aripiprazole in the treatment of patients with schizophrenia from the perspective of third-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
101
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(103 citation statements)
references
References 95 publications
(139 reference statements)
0
101
0
Order By: Relevance
“…The other models adapted the model of Furiak et al [75]. , with minor changes to the model structure (adding 2 side effects: hyperprolactinaemia and tardive dyskinesia).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other models adapted the model of Furiak et al [75]. , with minor changes to the model structure (adding 2 side effects: hyperprolactinaemia and tardive dyskinesia).…”
Section: Resultsmentioning
confidence: 99%
“…They set the baseline body weight and body mass index to patients individually, and simulated the changes in body weight and possible adverse events (AE). The model of Furiak et al [75]. had 3 health states (stable with or without side effects, and relapse requiring hospitalization) and 3 adherence levels, with a cycle length of 3 months.…”
Section: Resultsmentioning
confidence: 99%
“…The 24 studies included represent data from 14 countries: eight articles from the USA Tunis et al, 2006;Bounthavong & Okamoto, 2007;Edwards et al, 2008;Furiak et al, 2009;Ascher-Svanum et al, 2011;Ascher-Svanum et al, 2012;O'day et al, 2013), two from Canada (Cooper et al, 2008;Mcintyre et al, 2010) and Spain (Garcia-Ruiz et al, 2012;Treur et al, 2012) and one from Slovenia (Obradovic et al, 2007), Italy (Colombo et al, 2008), Greece (Geitona et al, 2008), Belgium (De Ridder & De Graeve, 2009), Brazil (Lindner et al, 2009), Mexico (Mould-Quevedo et al, 2009, China (Yang et al, 2009), Norway (Kim & Aas, 2011), Sweden (Lindström et al, 2011), Germany (Zeidler et al, 2013) and Vietnam (Anh et al, 2015). One study evaluated the cost-effectiveness of antipsychotics in European countries .…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…A utility component was found in 13 included studies, 12 of them reported effectiveness in measures of QALYs Knapp et al, 2008;De Ridder & De Graeve, 2009;Furiak et al, 2009;Lindner et al, 2009;Mcintyre et al, 2010;Ascher-Svanum et al, 2011;Lindström et al, 2011;Ascher-Svanum et al, 2012;Garcia-Ruiz et al, 2012;Treur et al, 2012;Zeidler et al, 2013) and one of them in DALYs averted (Anh et al, 2015). Regarding the source of data and modeling, three studies were based on Randomized Clinical Trials (RCTs) Tunis et al, 2006;Ascher-Svanum et al, 2011), three studies analyzed data from observational studies (Cooper et al, 2008;Knapp et al, 2008;De Ridder & De Graeve, 2009), nine studies built Markov models with literature data (Lindner et al, 2009;Mould-Quevedo et al, 2009;Mcintyre et al, 2010;Kim & Aas, 2011;Lindström et al, 2011;Ascher-Svanum et al, 2012;O'day et al, 2013;Zeidler et al, 2013;Anh et al, 2015) and nine studies only reported a decision analysis model with literature data (Bounthavong & Okamoto, 2007;Obradovic et al, 2007;Colombo et al, 2008;Edwards et al, 2008;Geitona et al, 2008;Furiak et al, 2009;Yang et al, 2009;Garcia-Ruiz et al, 2012;Treur et al, 2012). Most studies adopted time horizons of one year (Tunis et al, ...…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation